The Long-Term Loss of Smell and Taste in COVID-19 Patients – A Systematic Review and Meta-Analysis - Passos, Jaqueline Dal Curtivo; Borges, Yan Santos; Laureano, Henrique Aparecido; Guiloski, Izonete Cristina (ABCS Health Sciences, 2024)
Introduction: Olfactory symptoms have been reported as particular in COVID-19 patients. Objective: To synthesize and analyze the existing evidence on the monitoring loss of sense of smell and taste in COVID-19 patients, and for how long symptoms persist after the virus is no longer active in the organism. Methods: A search was implemented in PubMed, Embase, Scopus, Science Direct, and Web of Science databases. This systematic review and meta-analysis were conducted according to PRISMA, and the risk of bias was assessed through the Newcastle-Ottawa Scale. The review protocol is registered in PROSPERO. Results: Our systematic review included data from 14 articles with a total of 2143 participants. The most reported sensory symptom of COVID-19 was anosmia, which was detected in 1499 patients, being the only symptom to appear in all studies. Ageusia was detected in 595 patients, dysgeusia in 514 patients, and hyposmia in 209 patients. The studies provided the number of 729 patients with sensory symptoms during the acute COVID-19 infection of 15 days, and 1020 patients with lasting sensory symptoms, presenting sensory dysfunctions after the average latent period of 15 days of the acute COVID-19 infection. Conclusion: Evidence points to the loss or dysfunction of taste and smell as one of the symptoms of COVID-19 persisting for an average time of 15 days, with 44% of COVID-19 patients with persistent symptoms for more than 15 days. Nevertheless, most studies do not perform a follow-up with those patients. Therefore, further research on sensory symptoms and their follow-up is required.